Analisis Karya Lukis Berjudul “Kakak dan Adik” Berdasarkan Sudut Pandang De Witt H. Parker - Ricky, Yusnita Nur; Dawami, Angga Kusuma (Institut Seni Indoensia Surakarta, 2023)
The object of this research is the painting entitled “Kakak dan Adik” by Basuki Abdullah. To obtain theoretical results, the analysis is carried out by applying an aesthetic approach using the aesthetic form theory proposed by DeWitt H. Parker. This analysis is carried out with the aim of knowing the concepts or ideas and meanings that shape the beauty of the object used, the color chosen, and overall messages to be conveyed through this painting. These beauty can be seen through six principles regarding aesthetic forms in works of art, namely: The principle of Organic unity, the priciple of theme, the principle of thematic variation, the principle of balance, the principle of evolution, and the principle of hierarchy. Then from the use of these six principles, it was found that every element in the painting “Kakak dan Adik” indeed contains the values of beauty. That things can be seen from how these elements need each other in explaining the overall meaning of empathy for compassion and humanity. This feeling emerged when the painter was in a frenzy of social change which was the impact of changes in the nation’s economis system at that time.